A case of COVID-19 Reinfection and Systematic Review of Patterns of Reinfection. Issue 6 (4th November 2021) - Chamblain, Melissa; Dawkins, Elissa; Lane, Jason; Ghany, Reyan; Tamariz, Leonardo; Palacio, Ana; Guzman-Suarez, Belisa
Abstract: We present a case of a middle age Hispanic patient with COVID-19 reinfection. We conducted a systematic review of the literature of reinfection cases and found that women represent the majority of the cases and that reinfection usually presents with more severe disease, particularly among healthcare workers.